ANALISIS HUBUNGAN UMUR DAN JUMLAH ANAK TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER II - Putra, Bayu Pratama; Utama, Risma Putri; Noorma, Nilam; Yusuf, Sulfianti A. (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Anemia in pregnant women is defined as a condition where the hemoglobin level is less than 11 g/dl. The impact of anemia on pregnant women can be mild to severe. Data at Puskesmas Sangkunur still found pregnant women with anemia where in 2020 there were 35% of pregnant women with anemia, in 2021 there were 37% of pregnant women with anemia and in 2022 there were 35% of pregnant women with anemia. The purpose of this study was to determine the relationship between age and number of children to the incidence of anemia in second trimester pregnant women. The type of research is quantitative with a cross sectional approach. The research was conducted at the Sangkunur Health Center. The sample amounted to 30 people. The sampling technique used in this study was total sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between age (p value: 0.015) and the number of children (p value: 0.004) to the incidence of anemia. It is recommended that health workers be more active in providing health education related to the factors that cause anemia in pregnant women.Keywords: Anemia, Pregnant Women, Age